Implementasi Pendidikan Ilmu Sosial Dalam Pembelajaran Ilmu Sosial - Zainuddin, Muhammad; Muslihan, Muslihan (FAKULTAS TARBIYAH, 2020)
Social science education is a simplification of social science and is an interdisciplinary science so that social science education examines a problem from various social science perspectives in an integrated way. The purpose of social science education is to make good citizens in the sense of being able to understand differences and be able to provide appropriate problem solving because it is supported by information and facts that occur. in addition, the output of social science education is expected to be sensitive to social problems and social participation in society. on the other hand, its implementation in social science learning is faced with very complex obstacles, thus the nature and objectives of social science have not been fully achieved, so what has happened so far is that the output of social science education cannot be relied on for its contribution and even adds to the burden on society.